Una intervención leonesa en el Califato de Córdoba: a propósito de la identificación del conde Ibn Mama Duna Al-Qumis (Estudios humanísticos. Geografía, historia y arte, 1996)
This study tries to identify an important person: the so called Ibn Mama Duna "the christian" or al-Qumis in one of the most famous arab chronicle. In our opinion, he was Garcia Gómez, earl of Saldaña (955/960-1026?), who rebelled against Vermudo II, king of León, and was Almanzor's most important christian ally.